SYSTEM OF SUSTAINABLE INFRASTRUCTURE PLANNING ON DISTRICT MEDIUM-TERM - Jojok Widodo Soetjipto; Retno Utami A Wiyono; Paksitya Purnama Putra; Rindang Alfiah (UPT Penerbitan Universitas Jember, 2022)
The provision of district infrastructure requires detailed planning in preparing programs and budgets to encourage the equitable distribution of human settlement infrastructure development. The government has issued guidelines for preparing the RPIJM to harmonize the development plan, spatial plan, and Strategic Development Area plan. However, many problems must be resolved and are not proportional to the APBD/APBN revenues; therefore, it is necessary to formulate an appropriate RPIJM to support sustainable development. In this study, the RPIJM preparation refers to (i) policy directions and infrastructure strategic plans as well as the region's existing conditions analysis; and (ii) the design of infrastructure development. The RPIJM preparation must be carried out prudently because it involves a large budget, program of the community essential activities in solving existing problems and in sustainable development, synchronized infrastructure development for local and national governments, and the risk of failure in the management of its implementation. The results of the RPIJM are a proposed plan for the financing of the human settlements development sector, which includes: (i) Residential Area Development; (ii) Building and Environmental Management; (iii) Development of Drinking Water Supply Systems; and (iv) development of residential environmental sanitation. Recommendations of the RPIJM are compiled in the memorandum of the medium term program in human settlements, which outlines scenarios for district development in the publoc work-human settlements sector, proposals for investment based on needs, achievement targets by regional development goals and objectives, mechanisms of funding, handling priority, and investment program implementation.Keywords: RPIJM, sustainable development, development program, development funding